The Gospel of Matthew - Wilson, Walter T. 1962- (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2022)
volume 1. Matthew 1-13 -- volume 2. Matthew 14-28.
"The first volume of a magisterial commentary for scholars, students, pastors, and interested laypersons that interprets the Gospel of Matthew in its first-century context; and The second volume of a magisterial commentary for scholars, students, pastors, and interested laypersons that interprets the Gospel of Matthew in its first-century context"--
Includes bibliographical references and indexes
Keywords: Bible -- Commentaries; Kommentar